A comparison of biodegradation caused by Teredinidae (Mollusca:Bivalvia), Limnoriidae (Crustacea:Isopoda), and C. terebans (Crustacea:Amphipoda) across 4 shipwreck sites in the English Channel. (February 2019) - Knight, Kim Y.; Cousins, Thomas A.; Parham, David
Abstract: The need to protect underwater cultural heritage from biodegradation is paramount, however with many sites needing funding and support, it is hard to prioritise, thus the ability to identify high risk sites is crucial to ensure resources are best placed. In doing so a clear understanding of environmental conditions acting upon a site and abundance and composition of species present is essential to this identification. Therefore, the aim of this study was to assess the rate of biodegradation on four underwater cultural heritage sites in different marine environments by placing a series of wooden test panels in direct contact with the exposed structure on the sites. Upon recovery, test panels were photographed, X-rayed, and wood boring and sessile fouling species were identified and counted. The damage attributed to each species was recorded with CAD software. Results indicated a significant difference between sites, with HMS Invincible having the highest abundance of marine wood borers and the highest rate of surface area and volume degradation; whilst vestigial evidence of marine wood borers was found on the London, it would appear the environmental conditions had significantly impeded their survival. The study indicated further factors such as sediment type and coverage, availability of wood and the proximity of other colonised sites were also determining factors controlling the abundance of marine wood borers and the rate of biodegradation. Highlights: Teredinidae larvae showed no preference between the different wood types. Limnoria and C. terebans showed a preference to pine test panels over oak and elm. Sediment type and coverage is a significant factor in the survival of wooden underwater cultural heritage. Proximity to other colonised sites can increase species abundance and biodegradation. Exposed oak structure on HMS Invincible could lose 2% of surface area per month.